The influence of the husband’s role on the success of a pregnancy, childbirth to child development: Lessons learned from Ngemplak-1 Health Center - Hassanah, Aprilya; Seruni Angreni Susila; Wulandari Berliani Putri (BKM Public Health and Community Medicine, 2021)
Objective: Providing education through the "Father's Class" program to increase knowledge, care, awareness related to pregnancy and fostering husband empathy for pregnant women. Content: Maternal and infant deaths are still a health problem in Indonesia. This is a concern because maternal and infant mortality is an indicator of the degree of health and success of the implementation of health development of a country. Prevention that is being carried out in the form of standby villages, data collection of high-risk pregnant women has been and is being done to prevent the death of mothers and babies in the process of pregnancy, childbirth and after childbirth and procurement of classes of pregnant women. But in this case the prevention is only limited to pregnant women while for the role of couples to be less than optimal in supporting the health of pregnant women. The involvement of the husband in supporting the mother during pregnancy until after delivery is needed, because a husband not only meets the needs financially but pregnant women also need psychological and biological support. The mother's health affects the baby she will be born with. As a form of paternal support during pregnancy and after childbirth, procurement of the program "Father Class" becomes a place for husbands to get education. Procurement of "Father Class" becomes one of the innovations that can be done in village-level health services. At the village level, especially Javanese culture, it upholds family deliberation, so that the lack of husband's independence in decision making. This education is done to increase knowledge based on the importance of the role of the husband.